AJARAN IMAM ABU HANIFAH DALAM HUKUM ISLAM MELALUI MAZHAB HANAFI - Ningrum, Novita Ardiyanti; Kuraesin, Siti; Aisah, Putri Maharani Rahma; Prasetia, Riky; Anwar, Syahrul (Universitas Muhammadiyah Ponorogo, 2024)
This research is motivated by the fact that Islam recognizes the existence of four most prominent schools of thought, namely Hanafi, Maliki, Shafi'i, and Hambali. The scholars and Imams of the madhhab essentially discuss Islamic law. The discussion includes various concepts, including opinions, beliefs, ideologies, doctrines, teachings, understandings, and legal frameworks. Imam Hanafi is one of them, who has a rational style of fiqh and ushul fiqh thinking. This research aims to analyze how the biography and social and intellectual conditions at the time of Imam Abu Hanifah and how the pattern of ijtihad and examples of Imam Abu Hanifah's opinions in Islamic Law. This research uses a normative juridical approach and descriptive analysis method. Data was collected using literature study techniques, and using qualitative data analysis techniques. The results showed that Imam Abu Hanifah was a jurist who lived during the Umayyad and Abbasid dynasties, which were characterized by rapid social and intellectual development. He created the Hanafi school, known as flexible and moderate, which emphasizes the use of reason and ijtihad in determining Islamic law. In addition, the istihsan and urf methods that Imam Abu Hanifah introduced in fiqh allowed for the application of laws that were more in line with local social and cultural contexts. This shows that Imam Abu Hanifah valued and balanced customs and Islamic values.